2020
DOI: 10.1016/j.isci.2020.101460
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Hypoxia-Associated Signature in Pan-Cancer

Abstract: Summary Hypoxia is serving crucial roles in cancers. This study aims to comprehensively analyze the molecular features and clinical relevance of a well-defined hypoxia-associated signature in pan-cancer using multi-omics data. Data were acquired from TCGA, CCLE, GDSC, and GEO. RNA expression pattern, copy number variation (CNV), methylation, and mutation of the signature were analyzed. The majority of the 15 genes were upregulated in cancer tissues compared with normal tissue, and RNA expression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 40 publications
1
54
0
Order By: Relevance
“…Recently, the genes themselves were interrogated through an integrative analysis that assessed the correlation between the expression of each of the 15 genes with their methylation status and copy number variations (CNVs), among other features, in pan-cancer data and in repositories of cancer cell lines ( 181 ). All genes presented with CNVs, and their expression levels were reflective of their decreased promoter methylation in most cancers.…”
Section: Potential Application Of Hypoxia Biomarkers In Guiding Vascumentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the genes themselves were interrogated through an integrative analysis that assessed the correlation between the expression of each of the 15 genes with their methylation status and copy number variations (CNVs), among other features, in pan-cancer data and in repositories of cancer cell lines ( 181 ). All genes presented with CNVs, and their expression levels were reflective of their decreased promoter methylation in most cancers.…”
Section: Potential Application Of Hypoxia Biomarkers In Guiding Vascumentioning
confidence: 99%
“…All genes presented with CNVs, and their expression levels were reflective of their decreased promoter methylation in most cancers. Of relevance, the genes were associated with increased activation of oncogenic signaling pathways, and enrichment of malignant behaviors reflective of hypoxia, invasion and EMT ( 181 ). Furthermore, they acted as risk factors in more than half of gene-cancer pairs, supporting their cancer promoting role ( 181 ).…”
Section: Potential Application Of Hypoxia Biomarkers In Guiding Vascumentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptation of cancer cells to hypoxia facilitates tumor aggressiveness via driving genomic instability ( Reynolds et al, 1996 ), tumor progression, and therapeutic resistance, thus resulting in poor prognosis ( Luoto et al, 2013 ; Zhang et al, 2020 ). Indeed, a recent study revealed that hypoxia increases the mutational burden of breast cancer cells, as reflected by elevated frameshift insertions and deletions ( Hassan Venkatesh et al, 2020 ).…”
Section: Tumor Hypoxia Correlates With Genomic Instabilitymentioning
confidence: 99%
“…In the process of adapting to the hypoxic TME, cancer cells acquire invasive and metastatic properties ( 16 ). Interestingly, this hypoxia-associated signature has impressive pan-cancer predictive potential ( 17 ). Hypoxia regulates the mitochondrial activity of HCC cells through the hypoxia-inducible factor (HIF)/hes related family bHLH transcription factor with YRPW motif 1/PTEN induced kinase 1 pathway ( 13 ).…”
Section: Introductionmentioning
confidence: 99%